Effect of triangular pillar geometry on high- frequency piezocomposite transducers - Yin, Jianhua (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2010)
Piezocomposite materials are used extensively in biomedical transducer array fabrication. However, developing high-frequency piezocomposite materials for imaging systems is still a challenge due to the extremely small pillar dimensions required to avoid the interference from lateral resonances. The use of triangular pillar piezocomposite material has been shown to suppress lateral resonances that appear in square pillar composite designs. To further understand how the geometry of the pillars affects the lateral resonances, piezocomposite materials with triangular pillars of different angles have been simulated and fabricated. Simulations were performed on composite transducers of 70-microm pitch, 18-microm kerf width, and 100-microm thickness with isosceles triangular pillars in which the isosceles angle varied from 30 degrees to 60 degrees using a finite-element analysis. By varying the pillar geometry, the composite transducers show large differences in lateral resonances. The simulation results demonstrate that the composite with 45 degrees angle pillars has the lowest secondary pulse amplitude. The secondary pulse becomes larger when the pillar angle deviates from 45 degrees . To study whether the pillar height (which determines the resonance frequency) and aspect ratio would change the optimum angle, composites with 40-mum pitch, 15-microm kerf width, and 45-microm thickness were also simulated. Finally, the composite with triangle pillars was compared with composites with square and round pillars. The simulation results show that the 45 degrees triangular pillar geometry is, for high-frequency applications, the best configuration among all investigated in this work. Composite samples have also been fabricated to confirm results from finite-element modeling. Acoustical and electrical measurements were carried out to compare with theoretical predictions. Three composite transducers with pillar angles of 30 degrees, 45 degrees, and 60 degrees were fabricated using a dice-and-fill technique. The measured electrical impedances and one-way pulse responses agreed well with the theoretical predictions and confirm the optimal nature of the 45 degrees design